Desain dan Orientasi Arah Hadap Rumah Tradisional Malind Anim dalam Konteks Perubahan Iklim - Raubaba, Henry Soleman; Prianto, Eddy (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2024)
Climate change has placed significant pressure on the sustainability of traditional architecture, including the traditional Malind Anim houses in Merauke, South Papua. These houses, historically designed to adapt to the local climate, now face new challenges due to changes in temperature, rainfall, and extreme weather. This study aims to analyze the design and orientation of traditional Malind Anim houses in Kampung Wambi, Kampung Waan, and Kampung Toray in facing climate change. The method used is descriptive qualitative, with data collection techniques through direct observation and literature studies. This study found that the design of traditional Malind Anim houses that adopt certain orientations has the ability to reduce the impact of high temperatures and improve air circulation, thereby providing better thermal comfort for its inhabitants. Design elements such as the use of environmentally friendly local materials, effective cross-ventilation, and roofs designed to reduce heat significantly contribute to climate change adaptation. Additionally, this study also identifies that the local wisdom practices applied in the construction of these houses can serve as models for other regions facing similar climate challenges.